2015
DOI: 10.1177/1753465815617871
|View full text |Cite
|
Sign up to set email alerts
|

Management of advanced non-small cell lung cancers with known mutations or rearrangements: latest evidence and treatment approaches

Abstract: Precision oncology is now the evidence-based standard of care for the management of many advanced non-small cell lung cancers (NSCLCs). Expert consensus has defined minimum requirements for routine testing and identification of epidermal growth factor (EGFR) mutations (15% of tumors harbor EGFR exon 19 deletions or exon 21 L858R substitutions) and anaplastic lymphoma kinase (ALK) rearrangements (5% of tumors) in advanced lung adenocarcinomas (ACs). Application of palliative targeted therapies with oral tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
130
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 99 publications
0
130
0
1
Order By: Relevance
“…Considerable interest in lung ACAs harboring BRAF mutations has emerged due to the availability of therapeutic agents that can directly target BRAF or its downstream signaling constituents [7,8]. Involved in the RAS-MEK-ERK signaling pathway, BRAF is a serine/threonine kinase that lies downstream of RAS [9].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable interest in lung ACAs harboring BRAF mutations has emerged due to the availability of therapeutic agents that can directly target BRAF or its downstream signaling constituents [7,8]. Involved in the RAS-MEK-ERK signaling pathway, BRAF is a serine/threonine kinase that lies downstream of RAS [9].…”
Section: Introductionmentioning
confidence: 99%
“…16 However, advances in our understanding of the molecular basis of disease have led to targeted approaches for certain patients in whom an actionable genetic alteration is discovered and have been associated with improved prognosis. 27 For patients with an activating EGFR mutation, EGFR tyrosine kinase inhibitors demonstrated a survival advantage over chemotherapy. 16,27 Similarly, in patients in whom an ALK rearrangement is discovered, targeted therapy with an ALK inhibitor can confer improved outcomes.…”
Section: Prognosismentioning
confidence: 99%
“…25,26,35 While crizotinib is effective initially, patients ultimately develop resistance. [25][26][27]31,[33][34][35] In addition, spread of disease into the central nervous system (CNS) has been observed in patients whose disease progressed after treatment with crizotinib. 3,34 Clinical characterization of ALK-positive NSCLC patients who were treated with crizotinib beyond disease progression revealed that the brain was the most common single organ site for new lesions.…”
Section: Role Of Alk In Human Cancermentioning
confidence: 99%
“…At present, driver mutations are continuing to be identified; there are a number of clinical trials regarding targeted therapies in progress (10,11). Serine/threonine-protein kinase B-raf (BRAF) is a member of the RAF kinase family, which serves an important function in the MAPK signaling pathway (12,13).…”
Section: Introductionmentioning
confidence: 99%